REKONSTRUKSI KURIKULUM BAHASA ARAB DALAM MENINGKATKAN MAHARAH ISTIMA’ DI ERA TRANSFORMASI DIGITAL - Sari, Rizka; Siti Kholifah; Dicky Herlambang (Pusat Studi Ekonomi, Publikasi Ilmiah dan Pengembangan SDM, 2025)
This community service program aimed to reconstruct a digitally based Arabic language curriculum to enhance students’ istima’ (listening) skills at MIN 3 Rokan Hulu. The activities included curriculum analysis, teacher training, integration of digital media, and evaluation of the learning process. A descriptive qualitative method was used, employing interviews, observations, and documentation techniques. The implementation results showed that using digital media such as interactive audio, learning applications, and content visualization improved students’ participation and comprehension in listening activities. Teachers also responded positively to the use of technology after receiving mentoring. This curriculum reconstruction succeeded in creating a more contextual and communicative learning environment suited to students’ needs in the digital era. The program demonstrated that integrating technology into Arabic language instruction in madrasahs can be an effective, adaptive, and relevant approach to addressing the challenges of modern education.